2015
DOI: 10.1007/s00246-015-1178-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Acylated Ghrelin in Children with Pulmonary Hypertension Associated with Congenital Heart Disease

Abstract: This study aims to estimate plasma levels of acylated ghrelin in children with pulmonary hypertension (PH) associated with congenital heart disease (CHD) and to correlate the levels of acylated ghrelin with endothelin-1 (ET-1), nitric oxide (NO), and clinical hemodynamic parameters. We investigated the plasma concentration of acylated ghrelin, ET-1, NO, and the hemodynamic parameters in 20 children with CHD, 20 children with PH-CHD, and 20 normal children. Plasma-acylated ghrelin and NO levels were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Non‐CHD adults with HF reportedly have much lower ghrelin levels than those without HF . Moreover, plasma ghrelin levels are significantly high in children with CHD . Elevated ghrelin levels in these children might be related to malnutrition, growth retardation, and chronic shunt‐induced hypoxemia, wherein increased ghrelin might be a compensatory mechanism .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐CHD adults with HF reportedly have much lower ghrelin levels than those without HF . Moreover, plasma ghrelin levels are significantly high in children with CHD . Elevated ghrelin levels in these children might be related to malnutrition, growth retardation, and chronic shunt‐induced hypoxemia, wherein increased ghrelin might be a compensatory mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…24,29 Moreover, plasma ghrelin levels are significantly high in children with CHD. [8][9][10][11][12][13] Elevated ghrelin levels in these children might be related to malnutrition, growth retardation, and chronic shunt-induced hypoxemia, wherein increased ghrelin might be a compensatory mechanism. [8][9][10][11][12][13] In contrast, the mechanism underlying low ghrelin levels in adult patients with Fontan circulation and those with cyanosis is likely distinct.…”
Section: Ghrelin and Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, results vary significant between testing centers due to a lack of standards for ultrasonic inspection, differences in the quality of ultrasonic diagnostic equipment, the experience of the operator, and policies and guidelines at different centers which may influence the accuracy of ultrasonic diagnosis of fetal CHD. Recently, biomarkers such as increased acylated ghrelin [5], miR-19a [6] and beta human chorionic gonadotropin (HCGβ) [7], or decreased activity of BMP4 [8] and low levels of pregnancy associated plasma protein A (PAPP-A) [7] were found to be associated with fetal CHD, although their use as biomarkers for prenatal screening of fetal CHD is not specific.…”
Section: Circulating Lncrnas As Novel Noninvasive Biomarkers For Prementioning
confidence: 99%
“…Interestingly, previous and recent data reported conflicting results regarding the physiologic effect of ghrelin. Oppositely, Li et al found that plasma acylated ghrelin positively correlated with pulmonary hypertension associated with congenital heart disease 34. Recent evidence showed that both forms produced physiologic effects explaining the physiologic discrepancies in ghrelin effect.…”
mentioning
confidence: 99%